Letter - Atholl, Katharine Marjory Stewart-Murray, Duchess of, 1874-1960
1944-09-25 035-0082-008 The Spaniards you help us to aid here will carry away with them experiences and friendships which must work for international understanding and goodwill in their own country and in those countries to which they may emigrate in the years to come, and their gratitude for the help we give makes our work a pleasure. Yours sincerely, Katherine Atholl 292/946/35/82(viii)